Flooding Causes Analysis in The Engine Room of KM. Nusantara Akbar - Trika Pitana; Hari Prastowo; Muhammad Badrus Zaman; Aleix Nurwahyudi; Rachmat Gunawan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
This study analyzes about the cause of flooding in KM Nusantara Akbar’s engine room. However, this study mainly focuses on flooding that caused by shaft deflection. It was found that the cause of the flooding was packing, driven by a deflection shaft. Analysis was done by a review of the technical and non-technical factors. The analyze of engine room flooding is carried out by using 5 whys method to asses the root causes. The results show that the causes of flooding are reconditioned flange bolts that have been damaged and the addition of flax on the bearing shaft has to cope without straightening axle deflection itself, equipment to overcome the failure system is very less, the workplace is dirty and uncomfortable and happened miss communication between the crews.